2019
DOI: 10.1016/j.taap.2019.114709
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of BPA, BPAF and BPC on zebrafish estrogen receptors in vitro and in vivo

Abstract: The high volume production compound bisphenol A (BPA) is of environmental concern largely because of its estrogenic activity. Consequently, BPA analogues have been synthesized to be considered as replacement molecules for BPA. These analogues need to be thoroughly evaluated for their estrogenic activity. Here, we combined mechanism zebrafish-based assays to examine estrogenic and anti-estrogenic activities of BPA and two of its analogues, bisphenol AF (BPAF) and bisphenol C (BPC) in vitro and in vivo. In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 44 publications
4
22
0
2
Order By: Relevance
“…Many studies have reported that BPA has developmental effects in vivo at various concentrations across many species from invertebrates, to tunicates, amphibians, fish, chicken, mice, and monkeys ( Brannick et al, 2012 , Crump et al, 2016 , Huang et al, 2011 , Hunt et al, 2012 , Iwamuro et al, 2003 , Kontogiannatos et al, 2015 , Matsushima et al, 2013 , Mentor et al, 2020 , Moreman et al, 2017 , Qui et al, 2016 , Saito et al, 2012 , Tharp et al, 2012 , Tomohiro et al, 2003 , Wolkowicz et al, 2014 ). We and others have found that BPA and certain BPA analogs cause severe developmental defects in early Xenopus and zebrafish embryos, specifically inducing severe body axis and scoliosis-type spinal cord defects, decreased growth and body length and size, craniofacial malformations, eye dysplasia and pigmentation defects, loss of body pigmentation, gut and heart defects and edema, and high mortality rates ( Arancio et al, 2018 , Arancio et al, 2019 , Baba et al, 2009 , Huang et al, 2016 , Moreman et al, 2017 , Pinto et al, 2019 , Tomohiro et al, 2003 , Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many studies have reported that BPA has developmental effects in vivo at various concentrations across many species from invertebrates, to tunicates, amphibians, fish, chicken, mice, and monkeys ( Brannick et al, 2012 , Crump et al, 2016 , Huang et al, 2011 , Hunt et al, 2012 , Iwamuro et al, 2003 , Kontogiannatos et al, 2015 , Matsushima et al, 2013 , Mentor et al, 2020 , Moreman et al, 2017 , Qui et al, 2016 , Saito et al, 2012 , Tharp et al, 2012 , Tomohiro et al, 2003 , Wolkowicz et al, 2014 ). We and others have found that BPA and certain BPA analogs cause severe developmental defects in early Xenopus and zebrafish embryos, specifically inducing severe body axis and scoliosis-type spinal cord defects, decreased growth and body length and size, craniofacial malformations, eye dysplasia and pigmentation defects, loss of body pigmentation, gut and heart defects and edema, and high mortality rates ( Arancio et al, 2018 , Arancio et al, 2019 , Baba et al, 2009 , Huang et al, 2016 , Moreman et al, 2017 , Pinto et al, 2019 , Tomohiro et al, 2003 , Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
“…Because BPA and BPA alternatives are ubiquitous and in everyday products, it is crucial to examine their effects on embryonic development. Indeed, we and others have found that BPA and certain BPA analogs cause severe developmental defects in early Xenopus laevis (African clawed frog) and zebrafish embryos, specifically inducing growth, body axis, craniofacial, and eye defects, and high mortality rates ( Arancio et al, 2018 , Arancio et al, 2019 , Baba et al, 2009 , Huang et al, 2016 , Moreman et al, 2017 , Pinto et al, 2019 , Tomohiro et al, 2003 , Wu et al, 2017 ). It is unclear if the teratogenic effects of BPA and these newer BPA analogs are specific to frogs and fish, or can be observed across species.…”
Section: Introductionmentioning
confidence: 96%
“…In predicted binding to RXR-α, BPPH, BPAF and BPZ binding was scored as similar to that of prostacyclin and predicted binding to RXR-γ, BPAF and BPC was similar to that of the score for rosiglitazone. These differences have been independently verified in zebrafish ( Pinto et al, 2019 ), where BPA analogs such as BPC did not replicate the parent compound. Importantly, some species differences in receptor response to BPA complicate determination of mechanism.…”
Section: Case Study 2: Cardiovascular Disease (Cvd) and Non-eats Moda...mentioning
confidence: 93%
“…As an environmental endocrine disruptor, BPA has been shown to activate several types of receptors, including ER (Perera et al, 2017;Pinto et al, 2019). Although our in vitro studies have shown that BPA treatment can lead to apoptosis and pyroptosis in different gender nervous cells, and further con rmed the previous in vivo data that BPA can gender-dependently disrupt dendritic development and neurotransmitter homeostasis in the rat hippocampus (Zhang et al, 2019), the exact mechanism of BPA gender-speci c induction of apoptosis and pyroptosis of neuroblastoma cells remains unclear.…”
Section: Bpa Induces Damages In Neuroblastoma Cells In a Nonmonotonic And Gender-speci C Mannermentioning
confidence: 99%